1999
DOI: 10.1042/0264-6021:3440859
|View full text |Cite
|
Sign up to set email alerts
|

Direct interaction between p47phox and protein kinase C: evidence for targeting of protein kinase C by p47phox in neutrophils

Abstract: p47(phox) is an essential component of the NADPH oxidase, and phosphorylation of p47(phox) is associated with activation of the enzyme. Here we have used p47(phox) affinity chromatography to extract a p47(phox) kinase from neutrophil cytosol. The kinase activity was purified by gel filtration and Mini Q chromatography and shown to be indistinguishable from the catalytic fragments of protein kinase C (PKC)-beta(I), -beta(II) and -delta. The C-terminus of p47(phox) represented the site of interaction with PKC. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 7 publications
2
41
0
Order By: Relevance
“…PKC in PMN-PMN express ␣, ␤ I , ␤ II , ␦, and but not several other PKC isoforms (25,29,30,(43)(44)(45)(46)(47)(48)(49). We confirmed that PMN contain the former but lack ⑀, , , or isoforms (36,37).…”
Section: Pdb Binding-[supporting
confidence: 71%
“…PKC in PMN-PMN express ␣, ␤ I , ␤ II , ␦, and but not several other PKC isoforms (25,29,30,(43)(44)(45)(46)(47)(48)(49). We confirmed that PMN contain the former but lack ⑀, , , or isoforms (36,37).…”
Section: Pdb Binding-[supporting
confidence: 71%
“…Unsaturated fatty acids are well-established modulators of protein kinase C activity (McPhail et al 1984;O'Flaherty and Nishihira 1987;Shinomura et al 1991). PMA-induced respiratory burst activation requires protein kinase C and this activation step has been implicated in p47phox phosphorylation (Allard et al 1999;Reeves et al 1999;Korchak et al 1998). However, PMA-induced phosphorylation of p47phox is observed irrespective of cotreatment with methyl 9,10-/12,13-DiHOME ( figure 8).…”
Section: Discussionmentioning
confidence: 89%
“…Translocation of p47 phox to the membrane requires phosphorylation [55] of a number of serine sites located in its C-terminus, resulting in exposure of its SH3 domain, which binds directly to the p22 phox subunit of the flavocytochrome [56]. Neutrophils contain five of the eleven isoforms of PKC and there are several lines of evidence supporting a role for protein kinase C (PKC) a, bII, d and z in the phosphorylation of p47 phox [57] with a direct interaction between this substrate and the kinase been observed [58]. PKC is also capable of phosphorylating p47 phox at various sites, which are absolutely essential for activation and translocation of the protein [59].…”
Section: Discussionmentioning
confidence: 99%